Associations of number and position of tooth loss and quality of life in the Chilean population: a cross-sectional study - Andrés Celis Sersen; Jorge Celis-Dooner; Juan Pablo Vargas Buratovic; Claudio Carrasco Mococain; Beatriz Mellado Torres; Francisco Moreno Ferrer; Elizabeth López Tagle; Duniel Ortuno Borroto (BMC Oral Health, 2025)
Abstract Background Multiple studies have demonstrated the association between Quality of Life (QoL) and the prevalence of caries, periodontitis, and tooth loss. However, the role of the position and location of tooth loss in impacting QoL remains unclear. Aim To evaluate the association of tooth loss, including anterior losses, with Health-Related Quality of Life (HRQoL) and Oral Health-Related Quality of Life (OHRQoL) in Chileans aged 15 years and older who participated in the ENS 2016–2017. Methods In this cross-sectional study we included 5473 individuals enrolled in the last Chilean National Health Survey (ENS 2016–2017). HRQoL was measured using the EQ-5D questionnaire, while OHRQoL was assessed through a general question (GQ/ENS) and five specific questions (SQ/ENS). An analysis of variance test was performed to determine how difference or variation in the number(s) of teeth affected their HRQoL. Odds ratios with corresponding 95% confidence intervals were calculated using multinomial logistic regression to determine how and to what degree anterior tooth loss was associated both with HRQOL and OHRQOL in the study sample. Results The number of remaining teeth was significantly higher in the ‘No problems’ group across all EQ-5D dimensions, except Anxiety/Depression. The largest difference was in Self-care, where ‘No problems’ had a mean of 20.18 compared to 6.43 teeth in the ‘Problematic’ group. Anxiety/Depression showed higher odds of ‘Some problems’ with upper anterior tooth loss, while ‘Usual Activities’ showed higher odds of ‘problematic’ with lower anterior tooth loss. Participants with an ‘Excellent’ OHRQoL perception had a mean of 24.32 teeth. Also, upper and lower anterior tooth loss increased the odds of OHRQoL self-perception. Conclusions Tooth loss was associated with lower HRQoL and OHRQoL in some groups, with more remaining teeth associated with better outcomes, while anterior tooth loss was- linked to worse self-perceived oral health.